Neurogenic Differentiation of Bone Marrow Mesenchymal-Like Stem Cell Induced by Delonix regia Flowers Extract - Kartini Eriani; Irma Suryani; Al Azhar; Risa Nursanti; Ichsan Ichsan; Arief Boediono (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Stem cell technology has great potential in the effort to cure degenerative diseases. This study was done to determine optimum dose of flamboyant (Delonix regia) flower extract to induce proliferation and differentiation of mice (Mus musculus) bone marrow mesenchymal-like stem cell. Bone marrow cells were collected from mice by aspiration. Cells suspension (1 x 106) were poured into petri dishes containing 2 ml of modified Dulbecco's Modified Eagle's Media (mDMEM) and incubated overnight at 37 Â°C in a 5% CO2 incubator and microscopically observed. In quadriplicate, MSC were cultured in mDMEM containing D. regia flower extract of 0.0 (control), 0.4, 0.6, 0.8, and 1.0 mg/ml and incubated at 37 Â°C for 9 days. Population doubling time (PDT) and differentiated cell type were microscopically observed using HE staining on day 1 and 10. Data obtained were analyzed by ANOVA and Tukey test. The results showed that the addition of D regia flowers extracts 0.8 and 1.0 mg/ml significantly reduced PDT compared to that of 0.4, 0.6 and control. The extract, at 0.4 and 0.6 mg/ml, were able to induce MSC differentiation into fibroblast-like and nerve-like cells. In conclusion, D. regia flower extracts of 0.6, 0.8 and 1.0 mg/ml were able to stimulate MSC proliferation, but optimum dose for neurogenic differentiation was 0.6 mg/ml. This is the first to show potential of D. regia flower extract as neurogenic differentiatian inducer on mice MSC. These findings can be used as preliminary information for using the extract as cellular differentian inducer in basic and applicative reseach using stem cells.